Effect of HiFoliar nutrients and potassium nitrate on growth and yield characters of ber (Zizyphus mauritiana Lamk.) Cv Seo - Kumar, Sudhir; Kaurav, G.S.; Prasad, Rajendra (Indian Journal of Agroforestry, 2020)
The present study was carried out during 2012-13 to assess the effect of foliar spray of HiFoliar Nutrients and potassium nitrate (KNO3) on growth and yield of ber cv Seo. The experiment, conducted in completely randomized block design with four replications, comprised of twelve treatments [T1- HiFoliar 0.2% (H1K0), T2- HiFoliar 0.3% (H2K0), T3-HiFoliar 0.4% (H3K0), T4- KNO3 0.5% (K1H0), T5- KNO3 1.0% (K2H0), T6- HiFoliar 0.2% + KNO3 0.5% (H1K1), T7-HiFoliar 0.2% + KNO3 1.0% (H1K2), T8 HiFoliar 0.3% + KNO3 0.5% (H2K1), T9- HiFoliar 0.3% + KNO3 1.0% (H2K2), T10-HiFoliar 0.4% + KNO3 0.5% (H3K1), T11- HiFoliar 0.4% + KNO3 1.0% (H3K2), T12- Control (Water spray, H0K0)], imposed on ber plants when the fruits attained the diameter of >15 mm (marble stage). The plants were sprayed three times at the interval of fifteen days. The observations were recorded on growth and yield parameters of plant and fruit, respectively. The findings revealed that in ber HiFoliar Nutrients is only effective when used with KNO3. In general, most of the growth characters were influenced by either treatment T11 or T3 whereas fruit characters by treatment T5 and T11 except pulp/stone ratio and TSS in which treatment T9 showed its effectiveness. Considering the extra cost involved in treatment T11 by spraying HiFoliar Nutrients, the study concludes that three sprays of treatment T5 at the interval of fifteen days from the marble stage of fruits may be adopted for better growth, fruit quality and yield of ber (Zizyphus mauritiana Lamk.) Cv Seo.